Development of polarizable force fields and hybrid QM/MM methods for the study of reaction mechanisms - Webb, B (2003)
Computational chemists have successfully simulated many systems by applying the principles of quantum mechanics, while approximate molecular mechanical models have seen great utility in problems of biochemical interest. In recent years, a number of methods have been developed to combine the advantages of both techniques. In this study the so-called QM/MM method is developed and applied to the determination of the free energy of a simple Menshutkin SN2 chemical reaction. This is an extremely demanding process, well beyond the computational capacity of an average workstation, and thus a Beowulf-class Linux cluster is constructed to perform the calculations, and tested for a variety of computational chemistry applications. A number of methods for improving the QM/MM approach are considered in this work. The Fluctuating Charge, or FlucQ, polarizable molecular mechanics force field is implemented in a flexible manner within the CHARMM package and tested for a variety of systems, including the SN2 test case. Several drawbacks of the original method are addressed and overcome. Both molecular dynamics and Monte Carlo techniques are used within the QM/MM framework to investigate the SN2 reaction, and the two methods are compared. Techniques are developed and tested to increase the efficiency of QM/MC calculations to the point where they become competitive with QM/MD. Extremely expensive QM treatments are shown to be required to obtain accurate energies for the Menshutkin reaction. A method is developed and tested, and compared with the traditional ONIOM technique, for dramatically reducing the computational time required to use these treatments for QM/MC simulations, paving the way for fully ab initio high basis set QM/MM simulation.